Identities in Troubled Times: Minoritized Youth in Hong Kong’s “Summer of Protest” - Kerry J. Kennedy; Jan Christian Gube; Miron Kumar Bhowmik (Societies, 2023)
Discursive experiences can contribute to shaping lives and their identities. For minoritized youth in Hong Kong, the 2019 protest movement provided many such experiences, although very little has been heard about them. Instead, reporting has focused on the experiences of the dominant Chinese population. This paper aims to highlight the voices of minoritized youth in relation to the social movement that dominated Hong Kong in the second half of 2019. It is well recognized that identity is not fixed and that there are more likely multiple identities that transition from one to the other. Yet little is known about the influences on identity formation and the processes that underlie them. This was the issue addressed here. The paper draws on Lacan’s theory of identity in examining interviews involving minoritized youth and their engagement in Hong Kong’s 2019 protest movement. It shows how individual responses to the movement differed, how the movement challenged identities, and how these challenges were resolved.